1997
DOI: 10.1080/07924259.1997.9672557
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific gene regulation in early molluscan development

Abstract: In order to understand the processes that regulate cell-specific gene expression in early molluscan development, we studied the expression of tubulin genes in embryos of Patella vulgata (Gastropoda, Molluscs). Tubulin genes are fust expressed at the 32-cell stage, which is also the stage at which the embryonic transcription starts. At this stage expression of tubulin genes is observed exclusively in two cells in each quadrant, the trochoblasts. These cells, after one additional division, will differentiate int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The conclusion that similarities among trochophore larvae are the result of convergent evolution can be challenged experimentally, and it is not necessary to address the paleontological interpretations on which this scenario is based. Thus, for example, and Damen et al (1997) showed convincingly that the trochophores of annelids and molluscs share detailed similarities in the genetic regulatory circuitry underlying the development of trochophore-specific features. These features can hardly have arisen by convergence.…”
Section: Figmentioning
confidence: 94%
See 1 more Smart Citation
“…The conclusion that similarities among trochophore larvae are the result of convergent evolution can be challenged experimentally, and it is not necessary to address the paleontological interpretations on which this scenario is based. Thus, for example, and Damen et al (1997) showed convincingly that the trochophores of annelids and molluscs share detailed similarities in the genetic regulatory circuitry underlying the development of trochophore-specific features. These features can hardly have arisen by convergence.…”
Section: Figmentioning
confidence: 94%
“…Peterson et al, unpublished data). Most importantly, Damen et al (1997;see also van den Biggelaar et al, 1997) showed that the 5Ј upstream region of the Patella ␤-tubulin gene will correctly drive expression of a reporter construct not only in the trochoblasts of other molluscan embryos (including a polyplacophoran and a scaphopod), but in the trochoblasts of polychaete annelid embryos as well. Hence, the trochoblasts of annelid and molluscan embryos express the same lineage-specific gene, and expression is driven by the same set of transcription factors.…”
Section: Figmentioning
confidence: 99%
“…The prototroch is the primary ciliary band of spiralians (Nielsen 2005b). In support of ancestral regulatory entities, cis-regulatory sequences of a gastropod alpha-tubulin gene drive trochoblast expression in the primary ciliary band of various spiralians (Damen et al 1997). Secondary ciliary bands have different lineage origins among spiralians (Arenas-Mena et al 2007b;Henry et al 2007), although different lineages do not preclude deeper regulatory homology.…”
Section: Regulatory Evolution Of Indirect Developmentmentioning
confidence: 99%
“…The few studies on gene expression, e.g. on Patella [ 23 ] and Hydroides [ 20 , 24 , 25 ], are too scattered to contribute to the discussion.…”
Section: The Trochaea Theorymentioning
confidence: 99%
“…The few studies on gene expression, e.g. on Patella [23] and Hydroides [20,24,25] cells. The four apical cells are called the first micromere quartet (called 1a-1d or collectively 1q, their descendants are called 1q 1 and 1q 2 ) is referred to as the episphere (figure 2c).…”
Section: The Trochaea Theorymentioning
confidence: 99%